Micro-Analysis of Household Poverty and Inequality in Indonesia - Fitrawaty (JEJAK, 2024)
The quality of community resources becomes one of the determinants of a region's poverty rate. Gross participation rates for education in rural areas are much lower compared to urban areas, particularly for higher education, resulting in higher poverty rates in rural communities than in urban communities. Different perspectives lead to different thoughts. The ability of people to own assets in urban areas are lower than in those rural areas. Based on this, the poverty rate will be higher in urban areas than in rural areas. This study aimed to analyze the real causes of micro-poverty in North Sumatra Province. The research model utilized in this study was the Cross Section Approach. Data processing revealed that a relatively larger number of household members would lead the household into poverty, urban communities had a greater chance of entering the poverty trap, male household head had the likelihood for household to escape poverty, while for employment status. ‘Business owner with permanent/paid labors indicated the greatest likelihood to reduce poverty. The government needs to pay special attention to low-income people, encouraging policies that favor the poor. Providing direct cash assistance, encouraging the investment climate so that it can absorb labor, particularly those who do not possess entrepreneurial skills. The need for gender equality in various sectors to increase women's productivity